PENGARUH DUKUNGAN SOSIAL TERHADAP ADAPTASI SOSIAL ODGJ PASCA REHABILITASI DI PUSAT REHABILITASI WELAS ASIH - Indah Fitriyani; Yahdinil Firda Nadirah (STKIP Subang, 2025)
People with Mental Disorders (ODGJ) often face difficulties in readapting to society after undergoing rehabilitation. This study aims to determine the influence of social support on the social adaptation abilities of ODGJ after rehabilitation at the Welas Asih Rehabilitation Center. This research employed a qualitative approach through observations and interviews with the center's management. The results show that social support in the form of daily therapy, skills training, as well as family and community involvement plays an important role in improving the social adaptation of ODGJ. Continuous support also helps reduce the risk of relapse and encourages patient independence in living within the community.